Differential Modulation of the European Sea Bass Gut Microbiota by Distinct Insect Meals - Rangel, Fábio; Enes, Paula; Gasco, Laura; Gai, Francesco; Hausmann, Bela; Berry, David; Oliva-Teles, Aires; Serra, Claudia R.; Pereira, Fátima C. (Frontiers in Microbiology, 2022)
The aquaculture industry is one of the fastest-growing sectors in animal food production. However, farming of carnivorous fish strongly relies on the use of wild fish-based meals, a practice that is environmentally and economically unsustainable. Insect-based diets constitute a strong candidate for fishmeal substitution, due to their high nutritional value and low environmental footprint. Nevertheless, data on the impact of insect meal (IM) on the gut microbiome of farmed fish is so far inconclusive, and very scarce in what the concerns modulation of microbial-mediated functions. Here we use high-throughput 16S rRNA gene amplicon sequencing and quantitative PCR to evaluate the impact of different IMs on the composition and chitinolytic potential of the European sea bass gut digesta- and mucosa-associated communities. Our results show that insect-based diets of distinct origins differently impact the gut microbiota of the European sea bass (Dicentrarchus labrax). We detected clear modulatory effects of IM on the gut microbiota, which were more pronounced in the digesta, where communities differed considerably among the diets tested. Major community shifts were associated with the use of black soldier fly larvae (Hermetia illucens, HM) and pupal exuviae (HEM) feeds and were characterized by an increase in the relative abundance of the Firmicutes families Bacillaceae, Enterococcaceae, and Lachnospiraceae and the Actinobacteria family Actinomycetaceae, which all include taxa considered beneficial for fish health. Modulation of the digesta community by HEM was characterized by a sharp increase in Paenibacillus and a decrease of several Gammaproteobacteria and Bacteroidota members. In turn, a mealworm larvae-based diet (Tenebrio molitor, TM) had only a modest impact on microbiota composition. Further, using quantitative PCR, we demonstrate that shifts induced by HEM were accompanied by an increase in copy number of chitinase ChiA-encoding genes, predominantly originating from Paenibacillus species with effective chitinolytic activity. Our study reveals an HEM-driven increase in chitin-degrading taxa and associated chitinolytic activity, uncovering potential benefits of adopting exuviae-supplemented diets, a waste product of insect rearing, as a functional ingredient.